2014
DOI: 10.1093/europace/eut386
|View full text |Cite
|
Sign up to set email alerts
|

In silico ischaemia-induced reentry at the Purkinje-ventricle interface

Abstract: In a defined setting of ischaemia (phase 1B), a small amount of uncoupling between ventricular cells, as well as between Purkinje and ventricular tissue, may induce UDBs and reentry. Hyperkalaemia is also confirmed to be an important factor in the genesis of reentrant rhythms, since it regulates the range of coupling in which UDBs may be induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Because it is so difficult to predict how ion channel modification, studied in isolation, alters the functioning of the whole heart, computationally based modelling and simulation approaches have been developed and widely applied to link deviations in ion channel function to emergent electrical activity in cells, tissue and even simulated whole hearts. In the last 20 years, an explosion in the development of sophisticated models has occurred, concomitant with improved experimental techniques that have allowed identification and characterization of numerous ion channel subtypes and their regulation in the heart from multiple species (Romero et al 2010(Romero et al , 2011Bett et al 2011;Qu et al 2013;Verkerk & Wilders, 2013;Bueno-Orovio et al 2014;Glynn et al 2014;Greenstein et al 2014;Onal et al 2014;Ramirez et al 2014;Pathmanathan et al 2015;Besse et al 2011). Sophisticated ion channel models have even been developed that account for various genetic defects that alter the behaviour of ion channels.…”
Section: Cellular Models To Study Cardiac Arrhythmia Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is so difficult to predict how ion channel modification, studied in isolation, alters the functioning of the whole heart, computationally based modelling and simulation approaches have been developed and widely applied to link deviations in ion channel function to emergent electrical activity in cells, tissue and even simulated whole hearts. In the last 20 years, an explosion in the development of sophisticated models has occurred, concomitant with improved experimental techniques that have allowed identification and characterization of numerous ion channel subtypes and their regulation in the heart from multiple species (Romero et al 2010(Romero et al , 2011Bett et al 2011;Qu et al 2013;Verkerk & Wilders, 2013;Bueno-Orovio et al 2014;Glynn et al 2014;Greenstein et al 2014;Onal et al 2014;Ramirez et al 2014;Pathmanathan et al 2015;Besse et al 2011). Sophisticated ion channel models have even been developed that account for various genetic defects that alter the behaviour of ion channels.…”
Section: Cellular Models To Study Cardiac Arrhythmia Mechanismsmentioning
confidence: 99%
“…These complex ion channel representations have been incorporated into numerous cardiac model 'cells' from multiple species. The cellular level models have been widely replicated and coupled, creating mathematical representations of cardiac tissue in one, two or three dimensions, with the incorporation of complex anatomical heterogeneities including anisotropy, structural features and distinct cells with specifically associated electrophysiological characteristics (Trenor et al 2007;Romero et al 2009;Bers & Grandi, 2011;Niederer & Smith, 2012;Roberts et al 2012;Sugiura et al 2012;Trayanova et al 2012;Zhang et al 2012;Zhou & O'Rourke, 2012;Polakova & Sobie, 2013;Quail & Taylor, 2013;Romero et al 2013;Sato & Clancy, 2013;Tobon et al 2013;Ferrero et al 2014;Gomez et al 2014;Henriquez, 2014;Ramirez et al 2014;Trayanova & Boyle, 2014;Duncker et al 2015).…”
Section: Cellular Models To Study Cardiac Arrhythmia Mechanismsmentioning
confidence: 99%
“…Therefore an increasing number of computational models have incorporated and (in silico) analysed the CCS in order to understand the underlying pathologies and optimize treatment [ 38 41 ]. Experimental work [ 42 ] and modelling studies [ 43 , 44 ] on the influence of the PK micro-structure on arrhythmogenesis has focused on the coupling and electrical disturbances of the PVJs.…”
Section: Introductionmentioning
confidence: 99%
“…Less considered, however, is how variation in the severity of ischaemia (and its constituent electrophysiological impacts) controls the initiation of arrhythmia. Although many computational studies have demonstrated mechanisms of arrhythmia initiation due to ischaemia/infarction (for example [25][26][27][28]), the sensitivity of these mechanisms to different manifestations of the condition is far less clear. Studies that have considered the issue have suggested that for macro re-entry through an ischaemic region, hyperklaemia is most critical [29], whereas for re-entries residing within heterogeneous tissue, hypoxia is most important [30].…”
Section: Introductionmentioning
confidence: 99%